Redescription of Nanomysis siamensis W.M. Tattersall, 1921 (Crustacea: Mysida) after 100 years, with an update of its distribution in the Songkhla Lagoon System, southern Thailand - Yolanda, Rofiza; Sawamoto, Shozo; Lheknim, Vachira (Zootaxa, 2022)
Nanomysis siamensis W.M. Tattersall, 1921 is a shallow water mysid which was first described from the Thale Luang and the Thale Sap waters, Songkhla Lagoon System in southern Thailand. Recently, this species was captured further south, in the Thale Sap Songkhla waters. In this study, we provide updated records on spatial distribution of the species in the Songkhla Lagoon System. A total of 272 individuals of this species were observed, and illustrations of the body including all appendages are presented. Among them, the mandible, maxillule and maxilla are described for the first time. Morphological characteristics of N. siamensis are compared with other two known species of the genus Nanomysis.